Pengaruh Penerapan Model Pembelajaran Problem Based Learning (PBL)Terhadap Kemampuan Pemecahan Masalah dan Hasil Belajar Siswa Pada Materi Pertumbuhan dan Perkembangan Makhluk Hidup Dikelas XI - Rahmah, Syarifah; Ulfa, Syarifah Widya; R, Rasyidah (Madani: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to determine the effect of implementing the Problem-Based Learning (PBL) model on students' problem-solving abilities and learning outcomes in the growth and development of living things topic in grade XI of SMA Swasta Cerdas Murni. This study used a quasi-experimental method with a Non-Equivalent PretestPosttest Control Group Design. The study sample consisted of two classes: Grade XI Science 1 as the experimental class taught using the PBL model and Grade XI Science 2 as the control class taught using the conventional learning model, each with 29 students. Data collection was conducted through pretests and posttests to measure students' problem-solving abilities and learning outcomes. Data analysis was performed using normality tests, homogeneity tests, and One-Way ANOVA tests with a significance level of 0.05. The results showed that the implementation of the Problem-Based Learning (PBL) model had a significant impact on students' problem-solving abilities and learning outcomes. This is evident from the higher average posttest scores in the experimental class compared to the control class. The ANOVA significance value was 0.000 < 0.05, indicating a significant difference between the two classes. Thus, the application of the Problem-Based Learning model has proven effective in improving students' problem-solving skills and learning outcomes in the topic of growth and development of living things.